Folie à deux, delusional persolities aspects: the sisters Sabina and Úrsula Erickson case (Research, Society and Development, 2022)
The present article sets up a theoretical argument about the Folie à deux, a psychic phenomenon which the sharing of psychotics symptoms happens between two people. The Folie à deux was stated and discussed by Freud and Lacan, as well as the concepts postulated by Lèsegue and Falret. The development of this article shows the idea of neurotic and psychotic structure, articulating Folie à deux and the distinct ways of induced psychosis manifestation, in addiction to linking the event to a case study, the fact of the Erickson sisters. This article had as its primary objective to discuss about the Folie à deux phenomenon, using the bibliographic research as a method, along with the analysis a single case, using the qualitative approach. From the debate held in the article, it is verified that madness has its various connotations that can be attributed to a historical and cultural context, raising the need for a radical study of the ways that these so-called “madness” appear and a very deep analysis through the Folie à deux Phenomenon, leaving the questioning that the scarcity of theoretical content related to this theme is too large and there is the need for greater dissemination.